Outcome of Simple Bone Cyst Treated With Corticosteroid Injections - Muhammad Azeem Akhund1, Kishore Kumar2, Muhammad Faraz Jokhio3, Allah Nawaz Abbasi4, Muhammad Ali Jamali5 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Introduction:Simple bone cyst are lined by fibrous membrane and usually contain serous or serosanguinous fluid. Asymptomatic cysts do not require any intervention. However, if symptomatic then as corticosteroid injectio, bone grafting and curettage or injection of bone marrow can be considered as treatment options. Steroid injection therapy is a simple procedures with easy availability and low cost. The aim of this study was to determine the frequency of outcome in patients treated for simple bone cysts and to determine the association of various predicting factors with the positive outcomes. Materials and methods:This was a retrospective study conducted at Department of Orthopedics of a teaching hospital. Patients of either gender and aged 12 years or less diagnosed as having simple bone cyst on plain radiographs were, treated with cyst aspiration and steroid injection and had a follow up for at least 12 months were included. Treatment outcome to steroid injection was evaluated radiologically at every three months follow up till 12 months or more and was graded according to Neer’s scale. Grades I and II were good treatment response and grades III and IV were regarded as poor response. Results:Total 141 patients were included in the study. Humerus was the most common site of involvement followed by femur. Fracture was present in majority of the cases before treatment. Neer stage I was found in 57 (40.4%), stage II was found in 41 (29.1%), stage III was found in 28 (19.9%) and stage IV was found in 15 (10.6%) of the patients. Total 69.5% had good treatment response whereas 43 (30.5%) had poor treatment response. There was a significant association of healing with latent cyst (p value = 0.001) and unilocular cyst (p value = 0.000). Conclusion:Corticosteroid injection for simple bone cyst has high frequency of good response with significant association of cyst activity and cyst cavities with the treatment response.